Surface treatment for Schottky barrier photodetector based on Au/GaZnO nanorods/Au structure. (15th June 2017) - Song, Zehao; Zhou, Hai; Ye, Cong; Yang, Lu; Xue, Mengni; Mei, Jun; Wang, Hao
Abstract: In this paper, we will report the geometrical morphology, optical properties, electrical properties of the gallium doped ZnO nanorods (GZO NRs), as well as the performance of Au/GZO NRs/Au structure photodetector. We found that with the increase of the molar ratio of gallium, the length of the nanorods becomes smaller and the radial width increases, and the shape is more toward the hexagonal prism, and the grain radius increases. Also with the increase of the doping ratio, the optical absorption edge had a blueshift phenomenon, and the conductivity is enhanced. Moreover, in order to obtain the high performance of the photodetector, GZO NRs were treated by hydrogen peroxide and ohmic contact Au/GaZnO Nanorods/Au device was changed to a Schottky contact device, which showed a smaller dark current and faster response speed compared with ohmic contact device.